A novel extraction method for simultaneous determination of neonicotinoid insecticides and their metabolites in human urine. Issue 19 (30th April 2019) - Song, Shiming; He, Yuan; Zhang, Bo; Gui, Mingwei; Ouyang, Jiping; Zhang, Tao
Abstract : An LLME-LC-MS/MS method for the detection of trace levels of six neonicotinoid insecticides and their metabolites in human urine samples. Abstract : In this study, a novel method ( i.e., liquid–liquid micro-extraction, LLME) coupled to liquid chromatography tandem mass spectrometry is proposed for the simultaneous determination of urinary levels of six neonicotinoid insecticides (NEOs), namely, imidacloprid, clothianidin, acetamiprid, thiacloprid, thiamethoxam, and dinotefuran, and four metabolites, including 1-methyl-3-(tetrahydro-3-furylmethyl) guanidine, 1-methyl-3-(tetrahydro-3-furylmethyl) urea, 5-hydroxy-imidacloprid, and N -demethyl-acetamiprid has been developed. Ethyl acetate was used as the extraction solvent, and the supernatant was concentrated and dissolved by methanol. The method was validated for repeatability, reproducibility, linearity, and percent recovery. Satisfactory recovery of the NEOs and their metabolites (71–107%) was observed with intraday relative standard deviations (RSDs, n = 3) of 2–11% and inter-day RSDs ( n = 9) of 3–17%. Good linearity ( R 2 > 0.99) was obtained for all analytes. Limits of quantification and detection for all target analytes ranged from 0.01 ng mL −1 to 0.1 ng mL −1 and from 0.003 ng mL −1 to 0.03 ng mL −1, respectively. Trace levels of NEOs and their metabolites were found in human urine samples (mean: 0.06–1.99 ng mL −1 ). To the best of our knowledge, this study is the first to apply the proposed LLME method for simultaneous identification and quantification of NEOs and their metabolites in urine samples.